2007
DOI: 10.2105/ajph.2006.100164
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Patients Who Leave Acute-Care Hospitals Against Medical Advice

Abstract: Approximately 1 in 70 hospital discharges in the United States are against medical advice. Both hospital and patient characteristics were associated with these decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
168
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(200 citation statements)
references
References 13 publications
25
168
6
1
Order By: Relevance
“…Self-paying patients were three times more likely to take DAMA. This finding is comparable to previous studies (Ibrahim et al 2007;Nasir & Babalola 2008;Fiscella et al 2007). This factor is potentially open to modification as policies may be adopted to ease the burden of patients with financial difficulties.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Self-paying patients were three times more likely to take DAMA. This finding is comparable to previous studies (Ibrahim et al 2007;Nasir & Babalola 2008;Fiscella et al 2007). This factor is potentially open to modification as policies may be adopted to ease the burden of patients with financial difficulties.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, DAMA patients were found to be young males from low socio-economic status groups and without health insurance (Ibrahim et al 2007;Nasir & Babalola 2008;Pennycook et al 1992). …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…2 Patients who leave AMA may be at risk for adverse health outcomes leading to more frequent hospital readmissions and increased morbidity and mortality. [3][4][5][6] Prior retrospective chart review studies have found that the likelihood of AMA discharges is associated with hospital factors such as size and location 2 and patient factors such as mental illness, 4,7 substance abuse, 4,5,[7][8][9] gender, 2,5,7-9 income, 2,5 lack of medical insurance, 8,9 whether the individual is a Medicaid recipient, 2,9 race, 2,8-10 and young age 2,5,7,9,11 . One chart review found that providers document patients' reasons for leaving AMA as personal issues, financial problems, and legal matters.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Patients discharged AMA have higher rates of readmission, longer subsequent hospital stays, and worse health outcomes. 3,5,[8][9][10][11] Not unexpectedly, discharges AMA are associated with overall health costs of up to 50% greater than usual discharges.…”
mentioning
confidence: 99%